2020
DOI: 10.1515/ract-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

Understanding uranium oxide hardening during prolonged storage

Abstract: Uranium ore concentrates (UOCs), the product of uranium mining and milling, are primarily comprised of uranium oxide (U3O8 and UO2) or peroxide (UO4·4H2O and UO4·2H2O) compounds. Following production, UOCs are typically placed in storage until they are converted to uranium hexafluoride (UF6) at a uranium conversion facility. In this study, the chemical changes responsible for an interesting hardening phenomenon observed in UOCs stored for prolonged periods was investigated to understand underlying causes. Powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The provenance of nuclear material can be elucidated by signatures from industrial processes such as phase purity, synthetic route, precipitation conditions, thermal history, and the rate of oxidation. Of additional interest in determining material origin are signatures from temporal processes resulting from changes in chemical speciation due to environmental conditions. Previous U-oxide aging studies have demonstrated the utility of morphologic signatures, quantitative crystallography, thermogravimetric analysis, spectroscopic techniques, isotopic ratios, and predictive modeling in determining material speciation as a result of storage conditions. Each of these studies confirmed the formation of uranyl hydrate phases due to U-oxide aging.…”
Section: Introductionmentioning
confidence: 89%
“…The provenance of nuclear material can be elucidated by signatures from industrial processes such as phase purity, synthetic route, precipitation conditions, thermal history, and the rate of oxidation. Of additional interest in determining material origin are signatures from temporal processes resulting from changes in chemical speciation due to environmental conditions. Previous U-oxide aging studies have demonstrated the utility of morphologic signatures, quantitative crystallography, thermogravimetric analysis, spectroscopic techniques, isotopic ratios, and predictive modeling in determining material speciation as a result of storage conditions. Each of these studies confirmed the formation of uranyl hydrate phases due to U-oxide aging.…”
Section: Introductionmentioning
confidence: 89%
“…Improving understanding of the chemical and physical characteristics of nuclear materials remains an important goal in nuclear nonproliferation, nuclear forensics, and nuclear fuel cycle science. Within these domains, recent focus has been given to characterizing environmentally relevant changes in nuclear materials caused by exposure to atmospheric water vapor, UV light, or precipitation. Recent efforts investigated several fuel cycle-relevant uranium compounds and identified changes in chemical speciation and morphology when these compounds are exposed to various environmental conditions. Concerning the nuclear fuel cycle, environmentally driven alterations can affect the processability of uranium materials. For nuclear forensics, these chemical and physical changes could be used as an indicator of exposure to particular environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For nuclear forensics, these chemical and physical changes could be used as an indicator of exposure to particular environmental conditions. Overall, exposure to liquid water or atmospheric water vapor has been repeatedly observed to play a critical role in driving chemical speciation changes in fuel cycle-relevant uranium compounds. …”
Section: Introductionmentioning
confidence: 99%